Volumetric and viscometric study of binary mixtures of 1, 8-cineole with o-, m- and p-cresol at 303.15, 308.15 and 313.15K. (2nd January 2016) - Sharma, Sangita; Patel, Paras; Bhalodia, Jasmin
Abstract: The densities and viscosities of binary mixtures of 1, 8-cineole + o-, m- and p-cresol have been measured at 303.15, 308.15 and 313.15 K temperatures at atmospheric pressure. Using experimental values of densities, excess molar volume have been calculated. Similarly, from the densities and viscosities values, deviation in viscosity and excess Gibbs energy of activation for viscous flow has been calculated. Various viscosity correlating interaction parameters like Dolezalek–Schulze ( ), Grunberg–Nissan ( ), Tamura–Kurata ( ), Katti–Chaudhri ( ) and McAllister 3-body relation (, ) have been calculated. The Kendall–Munroe relation, Bingham relation and Arrhenius–Eyring relation have also been calculated. The calculated results were fitted using Redlich–Kister polynomial equation. The results show negative value for excess molar volume and positive value for deviation in viscosity and excess Gibbs energy of activation for viscous flow for all three binaries that indicates the presence of strong interactions between binary components.